An Analysis of Teachers’ Oral Corrective Feedback Strategies on Students’ Speaking Performace - Mulyadin, Asrul (International Journal Of Pedagogical Novelty (IJOPNOV), 2022)
This research were aimed to analyze the strategies used by the English teachers in giving corrective oral feedback on students’ speaking performance and their reasons tend to use particular strategies in giving oral corrective feedback on students’ speaking performance at SMA Adabiah 2.The type of this research was descriptive qualitative research. The data were collected through video recorder and interview. The sources of data were 5 English teachers at SMA Adabiah 2 Padang. The finding of this research indicated that oral corrective feedback strategies used by the teachers were explicit correction, recast, clarification request, metalinguistic clue, elicitation, and repetition. The most strategy used by the English teachers was recast and then explicit correction. Particular strategies used by the teacher because they know the level of the students’ motivation, condition, and the ability in understanding and receiving what has been given by the teacher. Keywords: Oral corrective feedback, speaking